A modified approach in the repair of type I and II truncus arteriosus to promote branch pulmonary arterial growth and limit early reoperationCentral MessagePerspective - Michael F. Swartz, PhD; Shuichi Yoshitake, MD; Jill M. Cholette, MD; Nader Atallah-Yunes, MD; Hongyue Wang, PhD; George M. Alfieris, MD (JTCVS Techniques)
Objective: Maintaining adequate branch pulmonary arterial growth is critical in preventing early (<3 years) right ventricular outflow tract reoperation after the repair of truncus arteriosus. We hypothesized that a modified truncus arteriosus repair keeping the branch pulmonary arteries in situ would promote branch pulmonary arterial growth and limit early right ventricular outflow tract reoperation. Methods: For infants requiring repair for type I and II truncus arteriosus, the truncal root was septated through a hockey stick incision keeping the branch pulmonary arteries in situ, the ventricular septal defect was closed, and a short aortic homograft was used to reconstruct the right ventricular outflow tract. Echocardiograms measured preoperative and follow-up branch pulmonary artery diameter. Results: Between 1998 and 2020, 41 infants were repaired using the modified approach (type I, 28; type II, 13). With a median follow-up of 11.6 (interquartile range, 3.1-15.5) years, there was no significant change between preoperative left pulmonary artery and right pulmonary artery Z-scores and their corresponding follow-up measurement (left pulmonary artery: 0.97, interquartile range, 0.6-1.6 vs left pulmonary artery: 1.4, interquartile range, –0.3 to 1.9) (right pulmonary artery: 0.6, interquartile range, –0.4 to 1.7 vs right pulmonary artery: 0.3 interquartile range, 0.5-0.9). Only 7.3% (n = 2) of follow-up right pulmonary artery Z-scores were less than 2.5 Z-scores below preoperative measurements. Four children (9.8%) required early right ventricular outflow tract reoperation. On multivariable analysis, larger conduit Z-scores were associated with greater time to right ventricular outflow tract reoperation (hazard ratio, 0.55, confidence interval, 0.307-0.984; P = .043). Conclusions: Maintaining the branch pulmonary arteries in situ at initial truncus arteriosus repair allows for branch pulmonary arterial growth, limiting early right ventricular outflow tract reoperation.